2018
DOI: 10.1007/s10162-017-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Nano-based Approach to Alleviate Cisplatin-Induced Ototoxicity

Abstract: Cisplatin-induced hearing loss is experienced by a high percentage of patients with squamous cell carcinoma undergoing cisplatin chemotherapy. A novel nano-construct capable of sequestering extracellular cisplatin was developed to combat this problem. The nano-construct consisted of superparamagnetic iron oxide nanoparticles (SPIONs) entrapped within polymeric micelles, which were formed from a glutathione diethyl ester-conjugated amphiphilic diblock copolymer. The glutathione-micelles were analyzed at the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Polyethylene glycol (PEG) provides both hydrosoluble and liposoluble characteristics to the particles, maintains electroneutrality, and avoids recognition by the reticulo-endothelial system to increase blood circulation time [ 107 ]. These properties have been exploited in multiple studies [ 18 , 40 , 47 , 50 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. The efficiency of doxorubicin (DOX) and indocyanine green loaded on 1,2- distearoyl-sn-glycero-3-phosphoethanolamine-N-PEG-SPIONS (SPION@DSPE-PEG/DOX/ICG) was compared to free DOX and SPION@DSPE-PEG NPs on glioma tumors in rats (n = 38) after the confirmation of their in vitro biocompatibility [ 66 ].…”
Section: Spions Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Polyethylene glycol (PEG) provides both hydrosoluble and liposoluble characteristics to the particles, maintains electroneutrality, and avoids recognition by the reticulo-endothelial system to increase blood circulation time [ 107 ]. These properties have been exploited in multiple studies [ 18 , 40 , 47 , 50 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. The efficiency of doxorubicin (DOX) and indocyanine green loaded on 1,2- distearoyl-sn-glycero-3-phosphoethanolamine-N-PEG-SPIONS (SPION@DSPE-PEG/DOX/ICG) was compared to free DOX and SPION@DSPE-PEG NPs on glioma tumors in rats (n = 38) after the confirmation of their in vitro biocompatibility [ 66 ].…”
Section: Spions Characteristicsmentioning
confidence: 99%
“…Polymers derived from amino acids were considered as SPIONs coating to increase their biocompatibility: gluthatione [ 58 , 62 ], glycine [ 82 ], glutamic acid [ 82 ], collagen [ 82 ], human serum albumin [ 18 , 82 ], aminosilane [ 112 ], and spermine [ 90 ] ( Table 2 ). The ability to cross a model of BBB in vitro of 5 SPIONs with different coatings in this category: 1—glycine, glutamic acid, bovine serum albumin (GGB), 2—glycine, glutamic acid, collagen (GGC), 3—glycine, glutamic acid, polyvinyl alcohol (GGP), 4—bovine serum albumin, polyethylene glycol (BPC), 5—collagen, polyvinyl alcohol, bovine serum albumin (CPB) showed that CPB-SPIONs, coated with collagen, have the highest in vitro cellular uptake and the best diffusion levels through BBB (2.7 g/mL of CPB were found after 2 h in the receiving well by a Ferrozine assay kit versus 1.9 of BPC and GGP, versus 1.5 of GGB, and versus 1.7 of GGC) [ 82 ].…”
Section: Spions Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanoparticles and nanomaterials have been used in the treatment of cancer to enhance targeted drug delivery and tumor specificity to minimize side-effects (28)(29)(30)(31)(32). The present study focuses on a particular class of laser-activated nanoparticles, specifically, a thermal ablation platform therapy using near-infrared excitation of gold nanorods (AuNRs), laser-activated nanotherapy (LANT).…”
Section: Introductionmentioning
confidence: 99%